The Difference in Views of Various Researchers - Vennu, Vishal (India’s New Drugs and Clinical Trial Rules: Perception and Perspectives of Indian Researchers, 2021)
About the new drugs and clinical trial rules of 2019 (NDCTR-19), no study surveyed the differences in views of various researchers, such as investigators, co-investigators, members of the ethics committee (EC), research assistants, coordinators, associates, and managers. The current study aimed to address this gap. The results of this study indicate that there is a significant variation in the views of different researchers about the changes of NDCTR-19. Future study is required on the larger sample at a national level to generalize the views of various researchers on the topic.